2021
DOI: 10.3389/frsen.2021.675323
|View full text |Cite
|
Sign up to set email alerts
|

The Directly-Georeferenced Hyperspectral Point Cloud: Preserving the Integrity of Hyperspectral Imaging Data

Abstract: The raster data model has been the standard format for hyperspectral imaging (HSI) over the last four decades. Unfortunately, it misrepresents HSI data because pixels are not natively square nor uniformly distributed across imaged scenes. To generate end products as rasters with square pixels while preserving spectral data integrity, the nearest neighbor resampling methodology is typically applied. This process compromises spatial data integrity as the pixels from the original HSI data are shifted, duplicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Despite being sparser than the SfM, the UAS LiDAR data are considerably higher in density than conventional airborne LiDAR data from manned aircraft due to the low altitude of the UAS data collection. For example, airborne LiDAR data over the same study area produced a point cloud with a density of 2-4 pts/m 2 [59]. Similarly, the authors in [64] reported a point density of 1-2 pts/m 2 from airborne LiDAR for wetlands in Eastern Canada.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Despite being sparser than the SfM, the UAS LiDAR data are considerably higher in density than conventional airborne LiDAR data from manned aircraft due to the low altitude of the UAS data collection. For example, airborne LiDAR data over the same study area produced a point cloud with a density of 2-4 pts/m 2 [59]. Similarly, the authors in [64] reported a point density of 1-2 pts/m 2 from airborne LiDAR for wetlands in Eastern Canada.…”
Section: Discussionmentioning
confidence: 81%
“…To classify the hummocks and hollows, the DSMs were first normalized in MATLAB v2020b (MathWorks, Natick, MA, USA) by subtracting the median elevation in a sliding window of 10 × 10 m [59]. Hummocks were defined as having a height range 5-31 cm above the median and hollows as >5 cm below the median.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their reliance on raster datasets, this correction method performs poorly in topographically complex areas, which cannot be compressed into a 2.5D raster [15]. Areas of geological interest and good exposure, such as cliffs, quarries and mines, often include sub-vertical faces with multiple orientations, so cannot be projected onto a 2D grid (DEM/orthomosaic) without introducing projective distortions that significantly degrade data quality [10,22,23]. To mitigate these issues and facilitate the collection of geological data from potentially important but otherwise inaccessible outcrops, a rapidly increasing number of methods are being developed to fuse remotely sensed hyperspectral data with dense 3D point clouds to create hyperclouds [8,10,17,23,24] that objectively record outcrop geometry and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Submerged aquatic vegetation (SAV) is vital to the health of aquatic ecosystems. It provides habitat and food for fauna, stabilizes sediments, modifies flow regimes, and improves water quality (Hestir et al, 2016;Shinkareva et al, 2019;United Nations Environment Programme, 2020). SAV is also facing severe threats in the forms of warming waters, increased water levels, invasive species, and human modification to waterways (Massicotte et al, 2015;Zhang et al, 2017;United Nations Environment Programme, 2020).…”
Section: Introductionmentioning
confidence: 99%